Adsorptive Removal of Azithromycin Antibiotic from Aqueous Solution by Azolla Filiculoides-Based Activated Porous Carbon - Davoud Balarak (18421452) (2021)
Due to the shortage of freshwater availability, reclaimed water has become an important source of irrigation water. Nevertheless, emergent contaminants such as antibiotics in reclaimed water can cause potential health risks because antibiotics are nonbiodegradable. In this paper, we report the adsorptive removal of azithromycin (AZM) antibiotics using activated porous carbon prepared from Azolla filiculoides (AF) (AFAC). The influence of the adsorption process variables, such as temperature, pH, time, and adsorbent dosage, is investigated and described. The prepared AFAC is very effective in removing AZM with 87% and 98% removal after the treatment of 75 min, at 303 and 333 K, respectively. The Langmuir, Temkin, Freundlich, and Dubinin–Radushkevich isotherm models were used to analyze the adsorption results. The Freundlich isotherm was best to describe the adsorption isotherm. The adsorption process follows second-order pseudo kinetics. The adsorption was endothermic (ΔH°= 32.25 kJ/mol) and spontaneous (ΔS° = 0.128 kJ/mol·K). Increasing the temperature from 273 to 333 K makes the process more spontaneous (ΔG° = −2.38 and −8.72 KJ/mol). The lower mean square energy of 0.07 to 0.845 kJ/mol confirms the process’ physical nature. The results indicate that AFAC can be a potential low-cost adsorbent of AZM from aqueous solutions. Other Information Published in: Nanomaterials License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/nano11123281